2010
DOI: 10.1177/1096348010382240
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Diversity Training

Abstract: The purpose of this study was to test the effectiveness of a diversity training exercise using perspective taking to increase positive attitudes toward non-English-speaking individuals. Ninety-six participants were given a pretest (survey) followed by the training and a posttest. Participants were randomly assigned as a “manager” or an “employee.” The managers were provided with a recipe and instructions in English, and the managers’ employees provided with the recipe and instruction in an abstract, non-Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…This change in attitudes is consistent with prior work on perspective taking that has shown positive shifts in the evaluation of ambiguously stereotyped groups (e.g., Galinsky & Ku, 2004;Galinsky & Moskowitz, 2000). For instance, Madera, Neal, and Dawson (2011) found that a perspective taking training exercise produced more positive attitudes toward non-English speakers by increasing empathy. Additionally, recent findings suggest that perspective taking can also indirectly change perceptions of minority members by increasing personal attraction to and support for organizations that endorse diversity initiatives (Madera, 2018).…”
Section: Personnel Assessment and Decisionssupporting
confidence: 89%
“…This change in attitudes is consistent with prior work on perspective taking that has shown positive shifts in the evaluation of ambiguously stereotyped groups (e.g., Galinsky & Ku, 2004;Galinsky & Moskowitz, 2000). For instance, Madera, Neal, and Dawson (2011) found that a perspective taking training exercise produced more positive attitudes toward non-English speakers by increasing empathy. Additionally, recent findings suggest that perspective taking can also indirectly change perceptions of minority members by increasing personal attraction to and support for organizations that endorse diversity initiatives (Madera, 2018).…”
Section: Personnel Assessment and Decisionssupporting
confidence: 89%
“…The most representative application would be in diversity training in either educational or workplace contexts. For instance, a recent study demonstrated that diversity training with English speaking participants through traditional perspective taking and role-playing significantly increased favorable attitude toward non-English speaking individuals in a workplace scenario (Madera, Neal, & Dawson, 2011). Our findings imply that using EE in similar diversity training settings would amplify these positive attitudes.…”
Section: Theoretical Implicationsmentioning
confidence: 52%
“…We note that some module content inclusion may be transferable across organizations. For instance, recognizing the similarities and differences between nested groups (e.g., race and sexual orientation), differentiating between different experiences among groups, considering empathy and perspective taking of individual experiences (Madera et al, 2011;Shukla, 2019), and recognizing subtle and implicit bias forms of discrimination in the workplace.…”
Section: A Path Forward: Diversity Module Building and Disseminationmentioning
confidence: 99%